Second Leadership Consultation Meeting hosted by Genetic Innovation, Marrakech 26 October 2023 - Aide Memoire - Das, Biswanath (CGIAR, 2023)
A high-level meeting between leaders from NARES in Africa, sub-regional organizations (ASARECA, CARDESA, CORAF), universities, development partners and CGIAR Genetic Innovation took place on 26 October 2023 at the Radisson Blu Hotel, in Marrakech, Morocco. This was the Second Leadership Consultation Meeting hosted by Genetic Innovation, following on the one held 27-28 June 2022 at the Trademark Hotel in Nairobi, Kenya. The Marrakech meeting took stock of progress made, issues to be addressed, and next steps to be taken to strengthen CGIAR Genetic Innovation collaboration with partners in Africa. Genetic Innovation is one of three CGIAR Action Areas.